Evaluation Capture, Evaluator Resilience, and the Need for Competencies of Evaluators - Frans Leeuw; Lyn Pleger (The Evaluation Center at Western Michigan University, 2023)
Evaluation capture is the situation in which evaluations and evaluators are surrounded by protocols, guidelines, standards, norms, criteria, templates, oversight and reviews from national and supranational organizations, governments, NGO's and agencies that ask for and finance monitoring and evaluation activities; these protocols and guidelines are sometimes labelled or part of 'evaluation policies.' The paper describes several developments in evaluation that contribute to this capture, referred to as mechanisms. The paper also addresses the question how to tackle this issue. The focus is on the role of the evaluator's resilience, while several competences of evaluators to realize that are also addressed.